Dakwah Toleransi Masyarakat Dalam Penyambutan Ekspedisi Biksu Thudong di Desa Purwahamba Tegal - Hanifah, Uli (IQTIDA : Journal of Da'wah and Communication, 2024)
Indonesia, as a country with a diverse religious belief society, has a high potential for conflict. Spiritual conflict is considered a chronic disease which can reappear suddenly without warning. To avoid this, harmonious social interactions and a deep understanding of tolerance between people are needed so that there will be no conflicts related to religious differences in the future. This research aims to analyze the implementation of tolerance-based preaching in welcoming Monk Tudong by managing the Purwahamba Indah (Pur'in) tourist attraction and the surrounding community. This research uses a qualitative approach with phenomenological methods as the basic framework. The results of this research are that tolerance-based preaching is an effort to invite someone to choose a spiritual path by emphasizing the values ​​of mutual respect without discrimination and continuing to spread peace and compassion among others. Tolerance-based da'wah is also used to improve the quality of the application of Islamic teachings. A brief explanation of the research background, methods used, findings, conclusions and recommendations to relevant agencies.